Robotic Versus Laparoscopic Resection for Mid and Low Rectal Cancers - Bedirli, Abdulkadir (JSLS, 2016)
BACKGROUND AND OBJECTIVES: The current study was conducted to determine whether robotic low anterior resection (RLAR) has real benefit over laparoscopic low anterior resection (LLAR) in terms of surgical and early oncologic outcomes. METHODS: We retrospectively analyzed data from 35 RLARs and 28 LLARs, performed for mid and low rectal cancers, from January 2013 through June 2015. RESULTS: A total of 63 patients were included in the study. All surgeries were performed successfully. The clinicopathologic characteristics were similar between the 2 groups. Compared with the laparoscopic group, the robotic group had less intraoperative blood loss (165 vs. 120 mL; P < .05) and higher mean operative time (252 vs. 208 min; P < .05). No significant differences were observed in the time to flatus passage, length of hospital stay, and postoperative morbidity. Pathological examination of total mesorectal excision (TME) specimens showed that both circumferential resection margin and transverse (proximal and distal) margins were negative in the RLAR group. However, 1 patient each had positive circumferential resection margin and positive distal transverse margin in the LLAR group. The mean number of harvested lymph nodes was 27 in the RLAR group and 23 in the LLAR group. CONCLUSIONS: In our study, short-term outcomes of robotic surgery for mid and low rectal cancers were similar to those of laparoscopic surgery. The quality of TME specimens was better in the patients who underwent robotic surgery. However, the longer operative time was a limitation of robotic surgery.